Kepemimpinan Kharismatik Kepala Madrasah dalam Meningkatkan Kinerja Tenaga Kependidikan di MAN 2 Ponorogo - Ardiansyah; Syafiq Humaisi; Sulaiman Abdul Rasid (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2026)
The leadership of madrasah principals plays a pivotal role in strengthening human resource quality and improving educational service effectiveness within Islamic educational institutions. This study examines the manifestations and implications of charismatic leadership in enhancing the performance of educational staff at MAN 2 Ponorogo. A qualitative descriptive approach was employed, involving the madrasah principal and staff members of the One-Stop Integrated Service Unit (PTSP) selected through purposive sampling. Data were collected through in-depth interviews, observations, and document analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña, comprising data condensation, data display, and conclusion drawing. The trustworthiness of the findings was established through source and method triangulation. The results indicate that the principal’s charismatic leadership is grounded in the Islamic values of siddiq (truthfulness), amanah (trustworthiness), tabligh (effective communication), and fathonah (wisdom and intelligence). These values are translated into exemplary conduct, persuasive communication, participatory decision-making, motivational and reward mechanisms, and the cultivation of a religiously oriented work culture. Such leadership practices contribute to increased staff engagement, responsibility, discipline, productivity, adaptability, loyalty, and professionalism. Moreover, they foster a collaborative, harmonious, and quality-oriented organizational climate that supports the continuous improvement of educational services. The study concludes that charismatic leadership embedded in Islamic values and participatory management practices constitutes an effective strategy for strengthening educational staff performance and advancing sustainable madrasah governance.